1977
DOI: 10.1177/000306517702500205
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Pathological Nostalgia

Abstract: Nostalgia is distinguished from homesickness from which it was originally derived, and from fantasy to which it is related. It is described as an affective-cognitive experience, usually involving memories of places in one's past. These memories are associated with a characteristic affective coloration described as "bittersweet". It is concluded that the locales remembered are displacements from objects whose representation was repressed. Nostalgia is a ubiquitous human experience that is evoked by particular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 2 publications
3
58
0
1
Order By: Relevance
“…Still other authors frame nostalgia as ambivalent, resulting from comparing the present to a favored past (Cavanaugh, 1989;Frijda, 2007;Johnson-Laird & Oatley, 1989;Mills & Coleman, 1994;Socarides, 1977;Werman, 1977). For example, Frijda (2007, pp. 87-88) describes nostalgia as coactivation of positive and negative affect, "a true bittersweet emotion: pain because of pleasures past, or pleasure because of pleasures that have gone.…”
Section: Historical Conceptions Of Nostalgiamentioning
confidence: 99%
See 1 more Smart Citation
“…Still other authors frame nostalgia as ambivalent, resulting from comparing the present to a favored past (Cavanaugh, 1989;Frijda, 2007;Johnson-Laird & Oatley, 1989;Mills & Coleman, 1994;Socarides, 1977;Werman, 1977). For example, Frijda (2007, pp. 87-88) describes nostalgia as coactivation of positive and negative affect, "a true bittersweet emotion: pain because of pleasures past, or pleasure because of pleasures that have gone.…”
Section: Historical Conceptions Of Nostalgiamentioning
confidence: 99%
“…Others argue that nostalgia is primarily positive, based on affection for the past (Batcho, 1998;Davis, 1979;Sedikides et al, 2004). For example, Davis (1979) describes nostalgia as "positively toned" (p. 18) and "almost never infused with those sentiments we commonly think of as negative" (p. 14).Still other authors frame nostalgia as ambivalent, resulting from comparing the present to a favored past (Cavanaugh, 1989;Frijda, 2007;Johnson-Laird & Oatley, 1989;Mills & Coleman, 1994;Socarides, 1977;Werman, 1977). Similarly, Holak and Havlena (1998) found that nostalgic narratives were judged to be affectively positive, and that nostalgic intensity increased with expressions of tenderness and elation.…”
mentioning
confidence: 99%
“…Nostalgia is a bittersweet feeling that consists of a longing for yesterday, evoking fond memories of the past (Werman, 1977). For marketing researchers, this concept is relevant for shaping the structures of consumer preference and has been studied since the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to speculate about the major triad being the "idealized" item, the norm of positive valence which is altered or "obscured" by the sad and negative intervals of the minor second or the major seventh, which are also the sharpest dissonances (Hutchinson & Knopoff, 1979;Kameoka & Kuriyagawa, 1969;Malmberg, 1918). Also, Werman (1977) sees nostalgia as "wistful pleasure, a joy tinged with sadness" (p. 393). Again, the analogy of the major triad representing happiness/joy, while the minor second and its inversion--the major seventh--represent the tinge of melancholy/sadness, is striking.…”
Section: ) Clashing Conventionsmentioning
confidence: 99%